A case of Graves' disease and type 1 diabetes mellitus following SARS-CoV-2 vaccination. Issue 125 (December 2021) - Patrizio, Armando; Ferrari, Silvia Martina; Antonelli, Alessandro; Fallahi, Poupak
Abstract: Autoimmune diseases, including autoimmune endocrine diseases (AIED), are thought to develop following environmental exposure in patients with genetic predisposition. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and vaccines against it could represent new environmental triggers for AIED. We report a patient, with history of vitiligo vulgaris and 8 years of type 2 diabetes, who came to our institution because of fever, weight loss, asthenia and thyrotoxicosis occurred 4 weeks later the administration of BNT162B2 (Pfizer-BioNTech) SARS-CoV-2 vaccine. Clinical, biochemical and instrumental work-up demonstrated Graves' disease and autoimmune diabetes mellitus. The occurrence of these disorders could be explained through different mechanism such as autoimmune/inflammatory syndrome induced by adjuvants (ASIA syndrome), mRNA "self-adjuvant" effect, molecular mimicry between human and viral proteins and immune disruption from external stimuli. However further studies are needed to better understand the underlying pathogenesis of AIED following SARS-CoV-2 vaccine. Highlights: SARS-CoV-2 vaccination could trigger autoimmune endocrine disease. Fifth case of Graves' disease following SARS-CoV-2 vaccination. First description of type 1 diabetes following SARS-CoV-2 vaccination. ASIA syndrome and molecular mimicry are potential mechanisms.